PENTINGNYA ASUPAN NUTRISI YANG BAIK PADA 1000 HARI PERTAMA KEHIDUPAN UNTUK MENCEGAH STUNTING - Naning Suryani; Lina Humaeroh; Ernawati; Demas Kusumawati (Jurnal Pengabdian Masyarakat DEDIKASI, 2021)
Stunting is a mismatch between age and physical development. Physically, body proportions look normal but growth will look abnormal after being measured and compared to children their age. The danger posed by the child's brain is difficult to develop and difficult to grow like other normal children. Stunting occurs from the time the mother is pregnant until the child is 2 years old, where at this time is the golden period, 80% of brain growth occurs in the first 2 years of a child's life. Stunting can be prevented by Maternal nutritional intake during pregnancy from the time it is tested positive for pregnancy until the delivery period must ensure the welfare of the child it contains. Early detection of pregnancy in the first trimester during a vulnerable period in the process of organogenesis / the process of forming organs and body organs that occurs around 7-8 weeks of gestation is an effort to deliver the fetus which is expected to have perfect shape. The mother's role in this period is very important. During pregnancy, the fetus gets nutritional intake from the mother. Giving birth to the perfect child requires a good process too. Mothers are expected to provide good nutrition during pregnancy to support fetal growth and development while in the womb